Economic Recovery Efforts through Tourism in the Bira Beach Area, Bulukumba Regency - Ahmad AB (Journal La Bisecoman, 2023)
Located in the enchanting province of South Sulawesi, Indonesia, lies the captivating Bulukumba Regency, a veritable haven for discerning travelers seeking to immerse themselves in a cornucopia of awe-inspiring natural wonders and a vibrant tapestry of cultural diversity. The advent of the global pandemic has undeniably caused significant disruptions within the tourism sector, thereby exerting a profound impact on the sustenance and well-being of local communities. The study utilizes qualitative methodologies to scrutinize the multifaceted role and profound influence of tourism within the designated region. This statement highlights the crucial significance of implementing sustainable tourism practices, fostering community engagement, and promoting equitable employment opportunities. The research endeavors to delineate a myriad of tactics aimed at fostering economic resurgence, encompassing initiatives such as programs focused on enhancing capabilities, the utilization of data to inform policy decisions, and harmonized endeavors to bolster the tourism sector. The research proposes a set of strategic measures aimed at maximizing the economic prospects of the tourism industry. These measures encompass the implementation of capacity-building initiatives targeted at local communities, with the objective of augmenting their skill sets and enhancing their employability. The imperative of guaranteeing equitable employment prospects and fostering sustainable practices cannot be overstated. In addition, it is imperative for the government and key players in the tourism industry to prioritize the implementation of a data-driven strategy in policymaking and coordination efforts, with the ultimate goal of rejuvenating the tourism sector in South Sulawesi Province.